111k views
3 votes
2/3 + 3k/4 = 71/12. How do I do this?

User Lulalala
by
4.4k points

1 Answer

5 votes

We want to solve the following equation:


(2)/(3)\text{ + }(3k)/(4)\text{ = }(71)/(12)

that is equivalent to :


(2)/(3)-(2)/(3)\text{ + }(3k)/(4)\text{ = }(71)/(12)\text{ - }(2)/(3)

that is


\text{ }(3k)/(4)\text{ = }(71)/(12)\text{ - }(2)/(3)

now, we will solve the right part of the equation:


\text{ }(3k)/(4)\text{ = }(71)/(12)\text{ - }(2x4)/(3x4)\text{ = }(71)/(12)\text{ - }(8)/(12)\text{ = }(71-8)/(12)\text{ = }(63)/(12)

that is :


\text{ }(3k)/(4)\text{ = }(63)/(12)

Now, we resolve for k:


\text{ k = }\frac{63\text{ x 4}}{12\text{ x 3}}\text{ = }(252)/(36)\text{ = 7}

we can conclude that :

k = 7

User Sevce
by
5.4k points